Effect Of Leadership Style And Work Motivation On Employee Work Discipline PT. Nata Bersaudara Sejahtera - Sahrul Ramdani; Rita Tri Yusnita; Arga Sutrisna (Journal of Indonesian Management, 2022)
This research was conducted with the aim of knowing the effect of Leadership Style and Work Motivation on Work Discipline of Employees of PT Nata Bersaudara Sejahtera. The method used in this research is a survey with a quantitative approach. Data collection techniques were obtained directly through questionnaires distributed to 89 respondents who were employees of PT Nata Bersaudara Sejahtera. The technique used in this research is path analysis. The results of the study indicate that: (1) Leadership style has a positive and significant effect on work motivation for employees of PT Nata Bersaudara Sejahtera; (2) Leadership style directly has a positive but not significant effect on the Work Discipline of PT Nata Bersaudara Sejahtera employees; (3) Work Motivation has a direct positive and significant effect on the Work Discipline of PT Nata Bersaudara Sejahtera employees; (4) Leadership style has a positive and significant effect on work discipline through the work motivation of employees of PT. Nata Bersaudara Sejahtera.